Search for very high energy gamma-rays from the z = 0.896 quasar 4C +55.17 with the MAGIC telescopes - Aleksic, J.; Ansoldi, S.; Antonelli, L.; Antoranz, P.; Babic, A.; Bangale, P.; Barres de Almeida, U.; Barrio, J.; Becerra, J.; Bednarek, W.; Berger, K.; Bernardini, E.; et al. (Oxford University Press, 2014)
The bright gamma-ray quasar 4C+55.17 is a distant source (z=0.896) with a hard spectrum atGeV energies as observed by the Large Area Telescope (LAT) on board the Fermi satellite. Thissource is identified as a good source candidate for very high energy (VHE; >30 GeV) gammarays.In general, VHE gamma-rays from distant sources provide a unique opportunity to studythe extragalactic background light (EBL) and underlying astrophysics. The flux intensity ofthis source in the VHE range is investigated. Then, constraints on the EBL are derived fromthe attenuation of gamma-ray photons coming from the distant blazar. We searched for agamma-ray signal from this object using the 35 h observations taken by the MAGIC (MajorAtmospheric Gamma-ray Imaging Cherenkov) telescopes between 2010 November and 2011January. No significant VHE gamma-ray signal was detected. We computed the upper limitsof the integrated gamma-ray flux at the 95 per cent confidence level of 9.4 × 10-12 and2.5 × 10-12 cm-2 s-1 above 100 and 200 GeV, respectively. The differential upper limitsin four energy bins in the range from 80 to 500 GeV are also derived. The upper limits areconsistent with the attenuation predicted by low-flux EBL models on the assumption of asimple power-law spectrum extrapolated from LAT data.